(untitled) (FAVE Sección Ciencias Veterinarias, 2016)
Resistance to anthelmintics in sheep nematode is widespread in central-northern Argentina and current major concern is the rise and spread of Haemonchus contortus carrying multiple resistance alleles. Currently, monepantel and derquantel are the only broad-spectrum anthelmintics without documentation of resistance in our country. With the first of these drugs, have already been registered cases of resistance in Uruguay and Brazil so it is critical update on the activity in the field of these anthelmintics. This study aims to test the effectiveness of monepantel after four years of use of this drug on an isolation of H. contortus with multiple resistance (macrocyclic lactones, closantel, levamisole and benzimidazole) and under conditions of reduced refugia. Two experiences, A and B (2014 and 2016 respectively), were carried out with lambs naturally parasitized and selected by the number of eggs per gram of feces (≥ 250). In both experiences, the test of reduction in egg counts after treatment with monepantel (2.5 mgr/Kg orally) comparing various formulas indicated that the drug remained with efficacy greater than 97% after four years of use to control this isolation of H. contortus under the field conditions of these studies.